2021
DOI: 10.3389/fmolb.2021.681938
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Growth and Division of Rat Gut Bacteria by D-Amino Acid-Based in vivo Labeling and FISH Staining

Abstract: Rat is a widely used mammalian model for gut microbiota research. However, due to the difficulties of individual in vitro culture of many of the gut bacteria, much information about the microbial behaviors in the rat gut remains largely unknown. Here, to characterize the in situ growth and division of rat gut bacteria, we apply a chemical strategy that integrates the use of sequential tagging with D-amino acid-based metabolic probes (STAMP) with fluorescence in situ hybridization (FISH) to rat gut microbiota. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…As expected, Gram-positive bacteria showed more efficient labeling than Gram-negative bacteria. This is consistent with previous fluorescent DAA labeling results (36,37) and can be explained by the fact that the PGN layers of Gram-positive bacteria are much thicker than those of Gram-negative bacteria. Further quantitative analysis of the results revealed that the number of labeled fluorine was ~10 8 atoms per bacterium (see table S2 for calculation).…”
Section: Labeling Bacterial Species In Vitrosupporting
confidence: 93%
“…As expected, Gram-positive bacteria showed more efficient labeling than Gram-negative bacteria. This is consistent with previous fluorescent DAA labeling results (36,37) and can be explained by the fact that the PGN layers of Gram-positive bacteria are much thicker than those of Gram-negative bacteria. Further quantitative analysis of the results revealed that the number of labeled fluorine was ~10 8 atoms per bacterium (see table S2 for calculation).…”
Section: Labeling Bacterial Species In Vitrosupporting
confidence: 93%
“…When combined with the use of FISH, a classical method to determine bacterial taxonomic information, the bacterial growth patterns at the genus and species level were identified. In their subsequent work, the above method was applied to analyze the growth and division patterns of human gut bacteria by colonizing germ‐free mice with human fecal microbiota and the growth and division patterns of rat gut bacteria [41f,42] …”
Section: Peptidoglycan Visualization and Bacterial Visualizationmentioning
confidence: 99%